Decellularization method influences early remodeling of an allogenic tissue scaffold. Issue 1 (10th May 2013) - Goktas, Selda; Matuska, Andrea M.; Pierre, Nicolas; Gibson, Tyler M.; Dmytryk, John J.; McFetridge, Peter S.
<x xml:space="preserve">Abstract</x> Extracellular matrix‐based biomaterials are currently pursued as an alternative to autologous transplants for the treatment of gingival recession and periodontal disease. These grafts offer improved tissue regeneration without the need for a second operative procedure used in current treatments to remove nonresorbable synthetic biomaterials. However, while decellularization is necessary to minimize the potential immunological impact, it can significantly modify the materials architectural and biochemical properties. By understanding cellular responses, it is possible to more specifically target varying clinical situations. These investigations assess a novel allogenic scaffold derived from the human umbilical vein and determine the effects of two decellularization approaches (osmotic lysis and the surfactant Triton X‐100) on the biological and mechanical properties during early remodeling events. Results show Triton X‐100 to be significantly more effective at extracting lipids, while the extraction of the scaffolds bulk protein, GAG and DNA similar between the two treatments. Once seeded, scaffolds prepared with osmotic lysis displayed increased cellular proliferation and reduced metabolic activity compared to scaffolds treated with surfactant. Biomechanical properties were largely preserved and similar between the two treatments. These results suggest that by optimizing scaffold processing conditions, biological events associated with remodeling can be modulated to tailor scaffold function for specific clinical applications. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 8–16, 2014.